2012
DOI: 10.1007/s10797-012-9222-3
|View full text |Cite
|
Sign up to set email alerts
|

Tax compliance under tax regime changes

Abstract: Abstract:In this paper we focus on the compliance effects of tax regime changes.According to the economic model of tax evasion, a tax reform should affect compliance through its impact on tax rates and incentives. Our findings demonstrate the importance of at least two further effects not covered by the traditional model: First, reform losers tend to evade more taxes after the reform. Second, a reform from a proportionate to a progressive system decreases compliance compared to a switch in the reverse directio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…While some of its main comparative static results-higher audit probabilities and fines increase compliance-have by and large been confirmed (see e.g., [17,18]), several authors have argued that observed levels of compliance are too high to be explained only by aversion to the risk of being fined (e.g., [19][20][21]). 6 Partially in response to the debate about the merits and demerits of the Allingham-Sandmo model, partially as independent efforts to understand the determinants of tax compliance, experimental designs have tended to become more involved, introducing inter alia public good elements (e.g., [17,19,23,24]), heterogeneous and earned income [23,25,26], richer tax schedules [26][27][28] or endogenous audit rules [29,30]. Other studies haven taken up psycho-social factors like the role of persuasion [31], moral constraints [32,33] and emotions [33,34], and still others investigated design factors such as the role of framing (e.g., [19,25,35]) or income source [25,36].…”
Section: Related Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…While some of its main comparative static results-higher audit probabilities and fines increase compliance-have by and large been confirmed (see e.g., [17,18]), several authors have argued that observed levels of compliance are too high to be explained only by aversion to the risk of being fined (e.g., [19][20][21]). 6 Partially in response to the debate about the merits and demerits of the Allingham-Sandmo model, partially as independent efforts to understand the determinants of tax compliance, experimental designs have tended to become more involved, introducing inter alia public good elements (e.g., [17,19,23,24]), heterogeneous and earned income [23,25,26], richer tax schedules [26][27][28] or endogenous audit rules [29,30]. Other studies haven taken up psycho-social factors like the role of persuasion [31], moral constraints [32,33] and emotions [33,34], and still others investigated design factors such as the role of framing (e.g., [19,25,35]) or income source [25,36].…”
Section: Related Literaturementioning
confidence: 99%
“…Over 90% of high-income taxpayers (72 out of 78) chose the weakly dominant strategy of not opting out and then contributing fully in the tax game interaction. 26 More than 80% of informed low-income taxpayers (93 out of 114) stated the corresponding rational belief that high-income taxpayers would in fact not take their outside option. Moreover, over 70% of informed low-income taxpayers (81 out of 114) also stated they would not opt out themselves if they were in the position of a high-income taxpayers under the prevailing tax structure, but would do so under a counterfactual tax rate of 50% for high-income taxpayers.…”
Section: Manipulation Checksmentioning
confidence: 99%
See 1 more Smart Citation
“…Tax evasion increases in income (Becker, Büchner et al 1987, Anderhub, Giese et al 2001; in the tax rate (Alm, Jackson et al 1992, Kleven, Knudsen et al 2011; (but see Anderhub, Giese et al 2001), and especially in reaction to an increase in the tax rate (Bernasconi, Corazzini et al 2014); if the tax regime changes from proportional to progressive tax (Heinemann and Kocher 2013); in the cost of effort (Bühren and Kundt 2014).…”
Section: C) Tax Evasionmentioning
confidence: 99%
“…Tax evasion is influenced by fairness considerations, and equality in particular. Tax evasion increases if, by the design of the experiment, others earn more (Doerrenberg and Duncan 2013, Bazart and Bonein 2014); if others underreport income (Wakolbinger and Haigner 2009, Bazart and Bonein 2014, Blaufus, Bob et al 2014, Lefebvre, Pestieau et al 2015; if a tax (Spicer and Becker 1980) or a tax reform is to the disadvantage of the participant (Heinemann and Kocher 2013); if lower income is taxed more heavily than higher income (Castro and Rizzo 2014); if participants compete with others who might evade taxes (Casagrande, Di Cagno et al 2015). However Fortin, Lacroix et al (2007) find that participants evade less taxes the more their peers evade, and vice versa.…”
Section: C) Tax Evasionmentioning
confidence: 99%